2009
DOI: 10.1667/rr1598.1
|View full text |Cite
|
Sign up to set email alerts
|

Lack of DNA Polymerase θ (POLQ) Radiosensitizes Bone Marrow Stromal CellsIn Vitroand Increases Reticulocyte Micronuclei after Total-Body Irradiation

Abstract: Mammalian POLQ (pol theta) is a specialized DNA polymerase with an unknown function in vivo. Roles have been proposed in chromosome stability, as a backup enzyme in DNA base excision repair, and in somatic hypermutation of immunoglobulin genes. The purified enzyme can bypass AP sites and thymine glycol. Mice defective in POLQ are viable and have been reported to have elevated spontaneous and radiation-induced frequencies of micronuclei in circulating red blood cells. To examine the potential roles of POLQ in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
67
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 30 publications
(38 reference statements)
5
67
0
Order By: Relevance
“…Thus, this polymerase may have acquired more fundamental role in DNA repair in higher plants. Mouse and human cell lines impaired in DNA pol theta are sensitive to bleomycin and ionizing radiation, implicating its function in some aspects of DSB repair [43], [44]. Studies in Drosophila melanogaster indicated that DNA Pol theta contributes to DSB repair by facilitating microhomology-mediated DNA end-joining [45], which is in accordance with our observation of a 10-fold decrease in the transformation efficiency of the Z16 mutant.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, this polymerase may have acquired more fundamental role in DNA repair in higher plants. Mouse and human cell lines impaired in DNA pol theta are sensitive to bleomycin and ionizing radiation, implicating its function in some aspects of DSB repair [43], [44]. Studies in Drosophila melanogaster indicated that DNA Pol theta contributes to DSB repair by facilitating microhomology-mediated DNA end-joining [45], which is in accordance with our observation of a 10-fold decrease in the transformation efficiency of the Z16 mutant.…”
Section: Discussionsupporting
confidence: 90%
“…Pol y has also been proposed to function in DNA repair. Indeed, this enzyme acts as a backup DNA polymerase during base excision repair in chicken DT40 cells 11 and nematodes 12 , but this functional observation has not been clearly demonstrated in mammals [13][14][15] . Studies in Drosophila have also suggested a role for Pol y in the repair of double-stranded breaks through the synthesis of DNA during alternative microhomology-mediated end joining 16,17 .…”
mentioning
confidence: 99%
“…Studies in Drosophila have also suggested a role for Pol y in the repair of double-stranded breaks through the synthesis of DNA during alternative microhomology-mediated end joining 16,17 . This potential DNA repair function could explain why mouse Pol y-deficient bone marrow stromal cells and human Pol y-depleted tumours exhibit increased sensitivity to ionizing radiation 13,14 . This role in the defense against ionizing radiation-induced DNA damage might also be due to the ability of the polymerase to perform translesion synthesis (TLS) past abasic sites and thymine glycol lesions, which are major products of reactive oxygen species-induced DNA damage and strong blockers to most other A-family as well as B-family replicative DNA polymerases 18,19 .…”
mentioning
confidence: 99%
“…Radiation induces DNA damage, chromosomal aberrations, cell cycle arrest, and/or cell death. In addition, exposure to radiation causes cells to generate reactive oxygen species (ROS; Wang et al, 2010b) and to form micronuclei (Goff et al, 2009). Bone marrow, although especially sensitive to radiation, possess pathways allowing repair of such damage (Ganasoundari et al, 1998;Manu et al, 2007;Greenberger and Epperly, 2009;Wang et al, 2010b).…”
mentioning
confidence: 99%